Enhancing Zero Trust Security: The Role of Conditional Access Policy Engines Beyond Identity - Madhulika Badanpet, MS (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Conditional Access Policy Engines represent a transformative approach to enterprise security, advancingbeyond traditional authentication methods to establish dynamic, context-aware protection frameworks.This article examines how these sophisticated systems evaluate multiple risk factors—including user identity, device posture, network context, and resource sensitivity